Cincinnati Police Department Traffic Stops Applying RAND's Framework to Analyze Racial Disparities - Ridgeway, Greg (RAND Corporation, 2009)
In 2002, the Cincinnati Police Department (CPD) joined with other agencies and organizations to improve police-community relations in the city. This report focuses on the analysis of racial disparities in traffic stops in Cincinnati. The authors find no evidence of racial differences between the stops of black and those of similarly situated nonblack drivers, but some issues can exacerbate the perception of racial bias.